The Toll Index. Innovation-based Economic Telemetry - Nikolaos Askitas; Klaus F. Zimmermann (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2011)
We present the operationalized Toll Index, which is a new type of early indicator for the German business cycle. We present the basic idea and document the power of the indicator for the purpose of nowcasting. The data will be regularly available at the IDSC, the data bank center of IZA and will be accessible there through the homepage. We further emphasize several policy recommendations regarding data.
Keywords: C82; E01; E32; 330; nowcasting; toll index; MAUT; economic telemetry; secondary data use; Konjunkturindikator; Straßenbenutzungsgebühr; Statistik; Straßengüterverkehr; Deutschland